2002
DOI: 10.1143/ptp.108.591
|View full text |Cite
|
Sign up to set email alerts
|

Open String Field Theory around Universal Solutions

Abstract: We study the physical spectrum of cubic open string field theory around universal solutions, which are constructed using the matter Virasoro operators and the ghost and anti-ghost fields. We find the cohomology of the new BRS charge around the solutions, which appear with a ghost number that differs from that of the original theory. Considering the gauge-unfixed string field theory, we conclude that open string excitations perturbatively disappear after the condensation of the string field to the solutions.Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(131 citation statements)
references
References 16 publications
4
123
0
4
Order By: Relevance
“…They derived them from a shift by a formal classical solution of open cubic string field theory, and in [9] it was shown that for a certain function f the cohomology is trivial (at ghost number one).…”
Section: Discussionmentioning
confidence: 99%
“…They derived them from a shift by a formal classical solution of open cubic string field theory, and in [9] it was shown that for a certain function f the cohomology is trivial (at ghost number one).…”
Section: Discussionmentioning
confidence: 99%
“…There was another class of papers [39][40][41], which attempted to find systematic analytic approximations to the exact solutions. Unfortunately, none of the above papers succeeded in proving Sen's conjectures perhaps with the exception of the third conjecture [42][43][44]. It is the goal of the present paper to provide the first nonsingular solution and prove Sen's first conjecture.…”
Section: Introductionmentioning
confidence: 89%
“…The appropriate one seems to be b 0 Φ = 0. cohomology is trivial [9]. Using that as the starting point one finds that apart for the usual energy momentum tensor there is an extra ghost contribution appropriate for the twisted b, c system with central charge −2.…”
Section: Feynman Rulesmentioning
confidence: 97%